Partnership Satisfaction in Living Kidney Donors - Nöhre, Mariel; Pollmann, Iris; Mikuteit, Marie; Weissenborn, Karin; Gueler, Faikah; de Zwaan, Martina (Frontiers in Psychiatry, 2018)
Due to organ shortage, living kidney donation is gaining increasing importance. Medical progress enables a successful transplantation between unrelated individuals, even individuals with AB0-incompatibilities. Spouses are the largest group of living kidney donors. We investigated the partnership status of 361 living kidney donors and assessed their partnership satisfaction with the German version of the Quality of Marriage Index. We compared the donor sample with a representative German population sample (n=1995). In addition, we compared donors who have donated to their partner (spouse donors) to those who have donated to someone else (non-spouse donors). In comparison to the population sample significantly more kidney donors were living in a relationship (82% versus 60%). Most donors reported an unchanged (76.6%) or improved (20.5%) relationship to the recipient since transplantation. A significantly higher partnership satisfaction could be found in the donor sample compared to the population sample which was mainly due to a higher partnership satisfaction of the spouse donors compared to the non-spouse donors. High partnership satisfaction in living kidney donors might be an indicator for a successful selection process before transplantation. Alternatively, kidney donation might have a stabilizing or even positive impact on the partnership. Due to the design of our study causative interpretations cannot be made. Therefore, prospective studies are required to assess partnership satisfaction before and after living kidney donation.